THE "SOCIETY OF RISK" AND PRACTICE OF ACTIVITIES IN NATURE: DIVING IN LITERATURE (Fiep Bulletin - online, 2015)
This article was written based on an outline of a literature review of the Doctoral thesis entitled "The Imaginarium of Sosial women practitioners of extreme risk - a dive into the world of free divers", with the aim of promoting an expansion in discussions respect of risk in contemporary society. At this time do not bother to discuss issues relating to gender and sport. Dipped himself in some concepts, such as "Risk Society", Reflectivity, Globalization, Individuation, in the approaches of Beck (1993) and Giddens (2002); the "substance of risk", according to Le Breton (2009); Social Risk Control, Spink (2001); and the notion of voluntary risk and its pleasures by Lupton & Tulloch (2002). It is believed that other authors contribute to the expansion of concepts and discussions about risk. However, we chose definitions that could help in the expansion of the reflections on the practice of sports that involve risk situations realized in Nature. From this brief dip in the literature it is possible to raise some questions as: - The experience of physical risk is deliberately chosen by practitioners of sport in Nature? - What is the risk for these practitioners? These questions emerge for building new visions regarding the risk in contemporary sports.
Keywords: Risk Cultivated. Activities in Nature. Sport.